Effect of some growth substances application on growth and seasonal yield of acid lime trees (Citrus aurantifolia Swingle) in Delta - Waleed Fouad Abobatta; Mahmoud A. Khodier; Hassan S. H. Ismail (Scientific Reports)
Abstract This work aims to investigate the impact of chitosan and hydrogen peroxide on the growth and seasonal yield of lime trees cultivated in commercial orchards in Qalyubiyya Governorate, Egypt, during the 2021 & 2022 seasons. The treatments include foliar spraying of two concentrations of CHI (100 & 200 ppm) and H2O2 (2 & 4 cm/L), either individually or in combination, at two distinct times, one month after fruit set (1st week of September) and after two months. The hypothesis was that applying chitosan and hydrogen peroxide would improve tree growth, fruit quality, and total production. The obtained results indicated that the combinations of CHI with H2O2 improved tree growth, leaf mineral composition, seasonal yield, and fruit quality parameters. CHI at 200 ppm + H2O2 at 4 cm/L was the most efficient treatment and achieved the largest tree canopy. Treatment of 100 ppm CHI with 2 cm/L H2O2 showed superior yield in terms of tree yield (23.56 & 29.64 kg/tree), total production (8.15 & 9.16 t/ha) compared to other treatments. Likewise, combinations of CHI and H2O2 improved fruit characteristics. Findings of this study demonstrated that the foliar application of CHI with H2O2 could be a promising application to improve seasonal lemon yield and fruit quality in commercial orchards.